Cancer-associated financial burden in German head and neck cancer patients - Rast, Jonas; Zebralla, Veit; Dietz, Andreas; Wichmann, Gunnar; Wiegand, Susanne (Frontiers in Oncology, 2024)
Background: Financial toxicity of cancer causes higher morbidity and mortality. As financial burden due to head and neck cancer (HNC) in European health care systems with legally established compulsory health insurance is still poorly understood, we setup an investigation to assess financial impact of HNC.Methods: Between 08/2022 and 03/2023 HNC consecutive patients (n=209) attending the cancer aftercare program of an university hospital in an outpatient setting were surveyed utilizing selfadministered questionnaires about their socioeconomic situation, income loss, and out-of-pocket payments (OOPP).The majority of HNC patients (n=119, 59.5%) reported significant financial burden as consequences of OOPP (n=100, 50.0%) and/or income loss (n=51, 25.5%). HNC patients reporting financial burden due to OOPP had on average 1716 € per year costs related to their disease, whereas patients reporting an income loss had a mean monthly income loss of 620.53 €. Advanced UICC (7 th edition, 2017) stage, T3 or T4 category and larynx/hypopharynx cancer are significant predictors of financial burden.HNC survivors suffer from significant financial burden after HNC treatment, even in Germany with a health care system with statutory health insurance. The findings from this study offer valuable insights for healthcare professionals and policymakers, helping them acknowledge the economic impact of HNC.